Studi Lineament dan Struktur Tektonik Daerah Tanjung Kurung, Kabupaten Kaur, Bengkulu - Silaban, Ganda Tua Gilbert; Sutriyono, Edy (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
Identification and interpretation of landscape lineaments and measurements of geological structural components in rock outcrops have been carried out in order to reveal the development of rock sequence deformation in the study area. This research was conducted in Tanjung Kurung Village and its surroundings. The regional observation area is included in the Manna Enggano Sheet Geological Map (Amin, T, C. et al, 1993), while tectonically it is located in the Bengkulu basin which previous researchers categorized as a fore-arc basin (Sapiie et al ., 2015). This study uses two approaches, namely lineament analysis with national digital elevation model (DEMNas) image interpretation and surface geological mapping with observation of rock outcrops or structures. The DEMNas image used in this research has been accessed from https://tanahair.indonesia.go.id/portal-web which is owned by the Geospatial Information Agency (BIG). The geological structure of the Bengkulu Basin is divided into two general directions, namely the North-West-Southeast and North-East-Southwest directions. Structures that trend northwest-southeast are the Tanjung Sakti fault and the Ketaun fault. These faults are directly related to the Semangko Fault pattern and the Mentawai Fault pattern (Yulihanto et al., 1995).